Printed from https://www.webqc.org

Chemical Equations Balanced on 02/16/25

 Equations balanced on the previous day Equations balanced on the next day
Balance the equation of any chemical reaction
C9H13 + KMnO4 + H2SO4 = C8H7O4 + MnSO4 + K2SO4 + H2O =>
80 C9H13 + 226 KMnO4 + 339 H2SO4 = 90 C8H7O4 + 226 MnSO4 + 113 K2SO4 + 544 H2O

C8H14O3N2 + O2 = NH3 + CO2 + H2O =>
2 C8H14O3N2 + 17 O2 = 4 NH3 + 16 CO2 + 8 H2O

Pb(C2H3O2)4 + Al2(SO4)3 = Pb2(SO4)4 + Al(C2H3O2)3 =>
6 Pb(C2H3O2)4 + 4 Al2(SO4)3 = 3 Pb2(SO4)4 + 8 Al(C2H3O2)3

Cu = Cu{2+} + e =>
Cu = Cu{2+} + 2e

Ca(OH)2 + CH3COOH = CaCH3COOH + H2 + O2 =>
Ca(OH)2 + CH3COOH = CaCH3COOH + H2 + O2

Si + NaOH = Si(OH)2 + Na =>
Si + 2 NaOH = Si(OH)2 + 2 Na

(CH3COO)2Mg + KHSO4 = MgKSO4 + (CH3COO)2H =>
(CH3COO)2Mg + KHSO4 = MgKSO4 + (CH3COO)2H

MgCl2 + NaOH = MgNa + Cl2 + OH =>
MgCl2 + NaOH = MgNa + Cl2 + OH

N2(g) + H2(g) = NH3(ag) =>
N2(g) + 3 H2(g) = 2 NH3(ag)

NiSO4 + NH4OH = [Ni(NH3)4]SO4 + H2O =>
NiSO4 + 4 NH4OH = [Ni(NH3)4]SO4 + 4 H2O

NaBr(s) + MnO2(s) + H2SO4(s) = Br2(l) + MnSO4(aq) + NaSO4(aq) + H2O(l) =>
2 NaBr(s) + 2 MnO2(s) + 4 H2SO4(s) = Br2(l) + 2 MnSO4(aq) + 2 NaSO4(aq) + 4 H2O(l)

NaOH + H2SO4 = Na2 + SO4 + H2O =>
2 NaOH + H2SO4 = Na2 + SO4 + 2 H2O

KMnO4 + FeSO4 + H2SO4 = K2SO4 + Fe2(SO4)3 + MnS04 + H2O =>
2 KMnO4 + 62 FeSO4 + 40 H2SO4 = K2SO4 + 31 Fe2(SO4)3 + 2 MnS04 + 40 H2O

KCl + HClO = KClO + HCl =>
KCl + HClO = KClO + HCl

CuS + NO3{-} = Cu + SO4{2-} + NO =>
CuS + 2 NO3{-} = Cu + SO4{2-} + 2 NO

Na3AsO3 + CuSO4 = Na2SO4 + Cu3(AsO3)2 =>
2 Na3AsO3 + 3 CuSO4 = 3 Na2SO4 + Cu3(AsO3)2

Mg(OH)2 + HNO3 = MgH + (OH)2NO3 =>
Mg(OH)2 + HNO3 = MgH + (OH)2NO3

Fe(iii)NO3 + Mg = Mg(NO3)2 + Fe(iii) =>
2 Fe(iii)NO3 + Mg = Mg(NO3)2 + 2 Fe(iii)

H2SO3 + OH = H2O + SO3 =>
H2SO3 + 2 OH = 2 H2O + SO3

K2CO3 + H2SO4 = K2SO4 + CO2 + H2O =>
K2CO3 + H2SO4 = K2SO4 + CO2 + H2O

V + HF = VF + H2 =>
2 V + 2 HF = 2 VF + H2

K2CrO4 + NaOH + Pb(NO3)2 = (PbOH)2CrO4 + KOH + NaNO3 =>
K2CrO4 + 4 NaOH + 2 Pb(NO3)2 = (PbOH)2CrO4 + 2 KOH + 4 NaNO3

sulfurdioxide + oxygen = SO3 =>
2 SO2 + O2 = 2 SO3

K2S(aq) + CaCl2(aq) = KCl + CaS =>
K2S(aq) + CaCl2(aq) = 2 KCl + CaS

[Zn(OH)4]{2-} + H3O{+} = [Zn(H2O)4]{2+} + H2O =>
[Zn(OH)4]{2-} + 4 H3O{+} = [Zn(H2O)4]{2+} + 4 H2O

KMnO4 + CuS + HNO3 = Cu(NO3)2 + H2O + KNO3 + Mn(NO3)2 + SO2 =>
6 KMnO4 + 5 CuS + 28 HNO3 = 5 Cu(NO3)2 + 14 H2O + 6 KNO3 + 6 Mn(NO3)2 + 5 SO2

K2(SO4) + H2O = K(OH) + H2SO4 =>
K2(SO4) + 2 H2O = 2 K(OH) + H2SO4

H2(g) + NO = H2O(l) + N2(g) =>
2 H2(g) + 2 NO = 2 H2O(l) + N2(g)

C2H3ClO2 + OH = H2O + C2H2ClO2 =>
C2H3ClO2 + OH = H2O + C2H2ClO2

HCl + Ag2NO3 = HNO3 + Ag2Cl =>
HCl + Ag2NO3 = HNO3 + Ag2Cl

Ca + Na2C2O2 = CaC2O2 + Na =>
Ca + Na2C2O2 = CaC2O2 + 2 Na

CH3OH + O2 = CO2 + H2O = CH4 + O2 = CO2 + H2O =>
2 CH3OH + 3 O2 = 2 CO2 + 4 H2O

S + NaOH + O2 = Na2SO4 + H2O =>
2 S + 4 NaOH + 3 O2 = 2 Na2SO4 + 2 H2O

H2O + Zn3Sb2 = Zn(OH)2 + SbH3 =>
6 H2O + Zn3Sb2 = 3 Zn(OH)2 + 2 SbH3

AlBr3 + Pb(OH)2 = Al(OH)3(s) + PbBr2(aq) =>
2 AlBr3 + 3 Pb(OH)2 = 2 Al(OH)3(s) + 3 PbBr2(aq)

Cl2(aq) + MgF2 = Mg2 + ClF2 =>
Cl2(aq) + 2 MgF2 = Mg2 + 2 ClF2

CH2OHCHOHCH2OH + HNO3 = CH2ONO2CHONO2CH2ONO2 + H2O =>
CH2OHCHOHCH2OH + 3 HNO3 = CH2ONO2CHONO2CH2ONO2 + 3 H2O

N3H5C2O2 + H2O = N2H4 + NH3 + H2C2O4 =>
N3H5C2O2 + 2 H2O = N2H4 + NH3 + H2C2O4

CuNO3 + Na3PO4 = CuPO4 + Na3NO3 =>
CuNO3 + Na3PO4 = CuPO4 + Na3NO3

H2CO3 = H2O + CO2 =>
H2CO3 = H2O + CO2

NAOH(aq) + Fe(NO3)3(aq) = NANO3(aq) + Fe(OH)3(s) =>
3 NAOH(aq) + Fe(NO3)3(aq) = 3 NANO3(aq) + Fe(OH)3(s)

Cu(NO3)2*3H2O + C6H8O7 = CuO + N2 + CO2 + H2O =>
9 Cu(NO3)2*3H2O + 5 C6H8O7 = 9 CuO + 9 N2 + 30 CO2 + 47 H2O

CuNO3 + Ca(OH)2 = CuOH + Ca(NO3)2 =>
2 CuNO3 + Ca(OH)2 = 2 CuOH + Ca(NO3)2

SNO + NF3 = SNF2 + N2O3 =>
3 SNO + 2 NF3 = 3 SNF2 + N2O3

Na3Po4 + K2SO4 = Na2SO4 + K3Po4 =>
2 Na3Po4 + 3 K2SO4 = 3 Na2SO4 + 2 K3Po4

NiCl2 + MgBr2 = NiBr2 + MgCl2 =>
NiCl2 + MgBr2 = NiBr2 + MgCl2

Na2CO3 + Cr2O3 + O2 = Na2CrO4 + CO2 =>
4 Na2CO3 + 2 Cr2O3 + 3 O2 = 4 Na2CrO4 + 4 CO2

MgBr2 + Ba(OH)2 = Mg(OH)2 + BaBr2 =>
MgBr2 + Ba(OH)2 = Mg(OH)2 + BaBr2

Cu(NO3)2 + H2O = Cu(OH)2 + N2O5 =>
Cu(NO3)2 + H2O = Cu(OH)2 + N2O5

Ca{+2} + O{-2} = CaO =>
Ca{+2} + O{-2} = CaO

1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56
Balance the equation of any chemical reaction
 Equations balanced on the previous day Equations balanced on the next day
Equations balanced on 02/09/25
Equations balanced on 01/17/25
Equations balanced on 02/16/24
Please let us know how we can improve this web app.
Menu Balance Molar mass Gas laws Units Chemistry tools Periodic table Chemical forum Symmetry Constants Contribute Contact us
How to cite?